Poster selection committee member - Zantides, Evripides (My University, 2026)
Emirates International Poster Festival (EIPF) is the first-of-its-kind creative platform in the MENA region developed to showcase and celebrate contemporary poster design from around the world. This is an initiative of the Cultural and Scientific Association (NADWA) in Dubai to expand creative expression and to promote graphic design practice and creative thinking in the MENA region. Posters are a unique form of visual communication for sharing information, human thoughts, response to local and global issues, promoting products or services.